Prevalence of metabolic syndrome among patients with type two diabetes mellitus attending Imam Hussein medical city in Karbala - Bader, Waleed (Karbala Journal of Medicine, 2021)
Background: The Metabolic syndrome is a cluster of risk factors that is responsible for the risk of coronary heart disease and stroke. Objective: determine the prevalence of Metabolic syndrome and its components among type two diabetes patients. Materials and methods: Across sectional study was conducted between February to August 2020 among 394 patients with type two diabetes were randomly selected in diabetic center of Imam AL Hussein Medical City in Karbala, Iraq . The demographic, clinical, and biochemical parameters were studied after obtaining informed consent from each patient. Metabolic syndrome was diagnosed according to the criteria of National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III). Result: The prevalence of metabolic syndrome was 92.7%. A total of 394 patients were included in the study,285(72.3%) were females with mean age (51.77±9.56) years. The most prevalent component of metabolic syndrome was elevated triglyceride (87.3%); followed by abdominal obesity (80.2%) and elevated blood pressure (71.6%). Conclusion: This study indicates significant prevalence of metabolic syndrome among type 2 diabetic patients; which proposing that diabetic patients are at increased risk of cardiovascular disease and other complications. Keywords: Metabolic syndrome; National cholesterol education program.